LO49: Can the HINTS exam rule out stroke in those with vertigo? A systematic review and meta-analysis. (May 2019) - Ohle, R.; Montpellier, R.; Marchadier, V.; Wharton, A.; McIsaac, S.
Abstract : Introduction : Acute vestibular syndrome (AVS - vertigo, nystagmus, head motion intolerance, ataxia, and nausea/vomiting) is a subset of patients presenting with vertigo. They are most often due to benign vestibular neuritis but can be a sign of a vertebrobasilar stroke. The HINTS (head impulse test, nystagmus, positive test of skew) exam has been proposed as an extremely accurate bedside test to rule out stroke in those presenting with AVS. Is the HINTS exam compared to MRI sufficiently sensitive to rule out vertebrobasliar stroke in an adult population presenting to the emergency department with AVS.Methods : We searched in Pubmed, Medline, Embase, the Cochrane database, and relevant conference abstracts from 1968 to December 2018 and performed hand searches. No restrictions for language or study type were imposed. Relevant studies were reviewed and data was extracted by two independent reviewers. Gold standard in ruling out stroke was; Negative late acute (72 hrs–10d) cranial MRI with DWI OR Negative early acute (0–72hrs) cranial MRI plus negative follow-up cranial MRI or clinical follow-up for TIA/stroke of ≥3 months. Included studies were prospective or retrospective with patients presenting with acute vestibular syndrome. Studies combined if low clinical and statstitical heterogeonity. Study quality was assessed using the QUADAS tool. Random effects meta analysis using Revman 5 and SAS9.3 was performed.Results : 6 studies with 715 participants were included( QUADAS 12/14 SD 1.2). Average study length 5.3 years ( STD 3.3 years) . Prevalence of vertebrobasilar stroke ranged 9.3-76% (Mean 39.1% SD 17.1). The most common diagnosis were vertebrobasilar stroke (Mean 34.8% SD 17.1%), peripheral cause (Mean 30.9% SD 16%). Intra cerebral haemorrhage (Mean 2.2%, SD 0.5%). Neurologist/neuro ophthalmologist performed the exam in 5/6 studies. 1 study reported a kappa between emergency medicine physician and neurologist of 0.24-0.41. The HINTS exam had a sensitivity of 96% (CI 95% 0.92-0.98, I2-0%), Specificity 91.4% (CI 95% 64.5-98.4% I2 94%). Positive likelihood ratio 11.9 ( CI 95% 2.9-48.8) and a negative likelihood ratio of 0.04 ( CI 95% 0.01– 0.14).Conclusion : The HINTS exam has excellent diagnostic accuracy for ruling out stroke when performed by a neurologist. The lack of ER proven diagnostic accuracy and high prevalence of serious diagnosis in those presenting with acute vestibular syndrome suggests care should be taken in ruling out central cause of dizziness in this population.